Extensive Reading using Graded Readers - Ruhil Amal, Azmuddin; Zuraina, Ali; Ezihaslinda, Ngah; Nooradelena, Mohd Ruslim; Liyana, Mohd Tamili (IJRSS & K.A.J., Pakistan, 2014)
Extensive Reading is particularly absent in tertiary education in Malaysia especially in public universities in the East Coast. This study explores the influence of ER on the students' reading performance and identifies the relevance of ER in increasing students' proficiency. ER was embedded into a 14 week course among a sample of 125 undergraduate students enrolled in the various English core university subjects. Edinburgh Project in Extensive Reading (EPER) was used as a guide in the selection of graded readers as well as the use of placement tests. Results indicated that students did significantly better in the post-test than in the pre-test.